A method for preparing OSA-modified debranched starch-reinforced gelatin hydrogel

Through the combination of OSA modified debranched starch and gelatin hydrogel, the problem of insufficient mechanical properties of gelatin hydrogel is solved, significantly improved its mechanical properties and thermal stability, and expanded its application scope in the fields of food and biomedicine .

CN118684909BActive Publication Date: 2025-01-17QINGDAO AGRI UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410958291.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-17
Publication Date
2025-01-17
Estimated Expiration
2044-07-17

AI Technical Summary

Technical Problem

Due to its poor mechanical properties, gelatin hydrogels limit their use range in a variety of applications, especially in environments where high mechanical strength, thermal stability and anti-biodegradability are required.

Method used

By introducing OSA modified debranched starch, it uses its hydrophilic carboxylic acid groups and hydrophobic long alkenyl chains to compound it with the gelatin hydrogel to form OSA modified debranched starch to strengthen the gelatin hydrogel, improving its mechanical properties and thermal stability Sex and elasticity. The process includes debranching of waxy corn starch, esterification of OSA octenyl succinate and compound preparation with gelatin.

Benefits of technology

It significantly improves the compressive stress, mechanical properties, thermal stability and anti-biodegradability of gelatin hydrogels, making them suitable for food packaging and biomedicine and other fields, and expands its application scope.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118684909B_ABST
    Figure CN118684909B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of modified debranched starch, and discloses a method for preparing an OSA-modified debranched starch-reinforced gelatin hydrogel, comprising the following steps: preparation of debranched starch: using waxy corn starch as a raw material, hydrolyzing the α-1,6 glycosidic bonds of amylopectin by pullulanase to produce debranched starch; preparation of OSA-modified debranched starch: esterification reaction between OSA and debranched starch occurs under mild alkaline conditions to replace part of the hydroxyl groups in starch; preparation of OSA-modified debranched starch-reinforced gelatin hydrogel: adding an OSA-modified debranched starch solution to a gelatin solution, and reacting to obtain an OSA-modified debranched starch-reinforced gelatin hydrogel. The present invention adopts the above-mentioned method for preparing an OSA-modified debranched starch-reinforced gelatin hydrogel, and the prepared hydrogel has excellent mechanical properties, thermal stability and elasticity, and has good biodegradability resistance, and can be widely used in food packaging, biomedicine and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of modified debranched starch, in particular to a method for preparing OSA modified debranched starch reinforced gelatin hydrogel. Background Art

[0002] Hydrogel is a highly hydrated network material with cross-linked polymer chains. The formation of hydrogel networks can be divided into three categories: natural polymers, synthetic polymers and semi-synthetic polymers (synthetic polymers with complex materials such as synthetic and natural elements). Natural polymer hydrogels commonly used in research include proteins (gelatin and collagen, etc.), xanthan gum, hyaluronic acid and alginate, etc. Synthetic polymer hydrogels include polyethylene glycol, polyvinyl alcohol, poly-2-hydroxyethyl methacrylate, etc. Semi-synthetic polymer hydrogels mainly include polymers combined with polyethylene glycol and cholesterol polysaccharides, etc. Hydrogels have many unique properties due to their high hydrophilicity, permeability, biocompatibility and low friction coefficient, and are widely used in drug delivery, cosmetics, absorbent resins, tissue engineering and food industry. However, most hydrogels are usually brittle and fragile because the polymer chains are randomly cross-linked, and are easily destroyed under certain pressure. Therefore, this greatly limits the potential application of hydrogels in terms of mechanical strength.

[0003] In the wide field of hydrogel research, gelatin-based hydrogels are of particular interest. Gelatin is a biopolymer extracted from collagen. Gelatin is widely used in the medical and food fields due to its biodegradability, good biocompatibility and film-forming properties. In addition, due to its foaming properties, gelatin can be used in fire retardants, crop protection covers, etc. Hide glue made using the viscosity of gelatin is more commonly used and more environmentally friendly than synthetic glue, and can be used as a sizing agent for papermaking to make emery cloth, sandpaper, and tape. The emulsification of gelatin can be used as a protective colloid and flocculant in cosmetics and coatings, and the higher the gel strength, the higher the emulsification ability of gelatin. However, the poor mechanical properties of gelatin hydrogels greatly limit their scope of application.

[0004] Nanocomposite hydrogel is a hot topic of research nowadays. Reducing the size of the filler to the nanoscale will have a more significant strengthening effect on the composite. It is also found that the smaller the particle size of the filler, the better the dispersibility in the composite, and the better the interaction with the composite. The hydrogel formed by the interaction between the nanofiller and the polymer network is called a nanocomposite hydrogel. The applicant's previous research found that short-chain starch can self-assemble in gelatin to form nanoparticles. Compared with pure gelatin hydrogel, the hardness and maximum compressive stress of the nanocomposite hydrogel are improved. Therefore, the present invention proposes to construct OSA-modified debranched starch, introduce hydrophilic carboxylic acid groups and hydrophobic long olefin chains, and compound them with gelatin hydrogel to strengthen the gelatin hydrogel and improve the mechanical properties of the gelatin hydrogel. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing an OSA-modified debranched starch reinforced gelatin hydrogel. The prepared hydrogel has excellent mechanical properties, thermal stability and elasticity, and has good resistance to biodegradation, and can be widely used in food packaging, biomedicine and other fields.

[0006] To achieve the above object, the present invention provides a method for preparing an OSA-modified debranched starch reinforced gelatin hydrogel, comprising the following steps:

[0007] S1. Preparation of debranched starch: using waxy corn starch as raw material, hydrolyzing the α-1,6 glycosidic bonds of amylopectin by pullulanase to produce debranched starch;

[0008] S2. Preparation of debranched starch modified with octenyl succinate OSA: OSA reacts with debranched starch under mild alkaline conditions to replace part of the hydroxyl groups in the starch;

[0009] S3. Preparation of debranched starch reinforced gelatin hydrogel modified with octenyl succinate (OSA): adding the debranched starch solution modified with OSA into the gelatin solution to react and obtain the debranched starch reinforced gelatin hydrogel modified with OSA.

[0010] Furthermore, the waxy corn starch was dispersed in a phosphate buffer solution at pH 4.6, and then gelatinized for 40 minutes under continuous stirring in a boiling water bath. The fully gelatinized starch was cooled to 58°C, and pullulanase was added for enzymatic hydrolysis for 24 hours. The obtained hydrolyzate was first roughly centrifuged to obtain a supernatant solution, which was inactivated by boiling water bath for 15 minutes, and then centrifuged to remove the enzyme. Anhydrous ethanol was added to the obtained hydrolyzate, allowed to stand for 30 minutes, and then centrifuged and freeze-dried to obtain debranched starch.

[0011] Furthermore, 5% debranched starch was placed in an oil bath at 121°C for 30 min, and then adjusted with 0.1M NaOH to maintain the solution pH at 8-9. Based on the mass of the debranched starch, different mass fractions of OSA were added to react. After the reaction, the precipitate was washed with ethanol and centrifuged to obtain a precipitate, which was then filtered and air-dried to remove water and ethanol, and finally freeze-dried to obtain OSA-modified debranched starch with different degrees of substitution.

[0012] Further, based on the mass of the debranched starch, the mass fraction of OSA is 3-50%.

[0013] Furthermore, the reaction conditions of debranched starch and OSA were 50° C. for 6 h, and then the pH was adjusted to 6.5 by HCl to terminate the reaction.

[0014] Furthermore, the specific operations of step S3 are:

[0015] ① Preparation of OSA-modified debranched starch solution: dissolve OSA-modified debranched starch in distilled water, treat the suspension with ultrasonic wave for 1 min, then heat at 120° C. for 2 min, and then cool to 45° C. to obtain OSA-modified debranched starch solution;

[0016] ② Preparation of gelatin solution: Add gelatin to distilled water, swell at room temperature for 30 minutes, and then heat at 45°C for 30 minutes to dissolve the gelatin to obtain a gelatin solution;

[0017] ③ Preparation of OSA-modified debranched starch reinforced gelatin hydrogel: Add OSA-modified debranched starch solution to gelatin solution, stir at 45°C for 10 min until completely mixed, pour into a mold, and let stand at 4°C for 12 h to form OSA-modified debranched starch reinforced gelatin hydrogel.

[0018] Furthermore, in step ③, the volume ratio of the OSA modified debranched starch solution to the gelatin solution is 1:1.

[0019] The present invention also provides OSA-modified debranched starch reinforced gelatin hydrogel prepared by the preparation method.

[0020] The advantages and positive effects of the preparation method of OSA-modified debranched starch reinforced gelatin hydrogel described in the present invention are:

[0021] 1. The compressive stress of the OSA-modified debranched starch-reinforced gelatin hydrogel in the present invention is significantly increased (883-2076 g), and can be increased by nearly 4 times at most.

[0022] 2. The hydrogel prepared by the present invention has excellent mechanical properties, thermal stability and elasticity, and has good resistance to biodegradation, and can be widely used in food packaging, biomedicine and other fields.

[0023] 3. The introduction of OSA modified starch in the present invention not only significantly improves the mechanical properties, thermal stability and elasticity of gelatin hydrogel, but also greatly enhances its anti-biodegradability, expanding the application range of gelatin hydrogel under variable environmental conditions.

[0024] 4. The addition of OSA modified starch in the present invention greatly optimizes the performance of gelatin hydrogel, opening up new avenues for its application in key fields such as food packaging and biomedicine. In particular, in the biomedical field, the modified gelatin hydrogel has become an ideal choice for applications such as drug delivery systems, tissue engineering scaffolds and wound dressings due to its good biocompatibility and biodegradability, providing an innovative solution for tissue repair and regeneration.

[0025] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The gel-forming properties of gelatin hydrogels enhanced by debranched starch modified with OSA at different concentrations (5%, 10%, 30% and 50%) in the embodiments of the present invention;

[0027] Figure 2 : is a stress-strain curve of gelatin hydrogels reinforced with different OSA mass fractions (3%, 25% and 50%) and different concentrations of OSA-modified debranched starch in the embodiments of the present invention, wherein 0 is pure gelatin hydrogel, the concentration of OSA-modified debranched starch in A is 5%, the concentration of OSA-modified debranched starch in B is 10%, the concentration of OSA-modified debranched starch in C is 30%, and the concentration of OSA-modified debranched starch in D is 50%;

[0028] Figure 3 The figures are dynamic rheological diagrams of gelatin hydrogels reinforced with different OSA mass fractions (3%, 25% and 50%) and different concentrations of OSA-modified debranched starch in the embodiments of the present invention, wherein 0 is pure gelatin hydrogel, the concentration of OSA-modified debranched starch in A is 5%, the concentration of OSA-modified debranched starch in B is 10%, the concentration of OSA-modified debranched starch in C is 30%, and the concentration of OSA-modified debranched starch in D is 50%. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0030] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0031] Example 1 Preparation of OSA-modified debranched starch-reinforced gelatin hydrogel

[0032] 1. Preparation of debranched starch with different degrees of polymerization:

[0033] The present invention uses waxy corn starch as a raw material, and produces debranched starch by hydrolyzing the α-1,6 glycosidic bonds of amylopectin by pullulanase. Waxy corn starch (10 g) is dispersed in 100 mL of phosphate buffer (0.1 M, pH 4.6), and then continuously stirred and gelatinized for 40 minutes in a boiling water bath. The fully gelatinized starch is cooled to 58° C., and pullulanase (6692NPUN) is added for enzymatic hydrolysis for 24 hours. The obtained hydrolyzate is first roughly centrifuged (3500 g, 1 min), and the supernatant solution is boiled in water and the enzyme is inactivated for 15 minutes. Then centrifugation (3500 g, 1 min) is continued to remove the enzyme. 15 mL or 30 mL of anhydrous ethanol is added to the obtained hydrolyzate (10 mL), and the mixture is allowed to stand for 30 minutes, followed by centrifugation (3500 g, 5 min), and the precipitate and supernatant obtained are freeze-dried respectively. The control mixed debranched starch is obtained by directly freeze-drying the hydrolyzate. The yield of debranched starch with different degrees of polymerization was calculated by dividing the weight of debranched starch by the weight of initial starch.

[0034] 2. Preparation of high polymerization degree octenyl succinic acid modified debranched starch:

[0035] 5% high-polymerization debranched starch was placed in an oil bath at 121°C for 30 minutes, and then adjusted with 0.1M NaOH to maintain the solution pH at 8-9. Based on the mass of debranched starch, different mass fractions (3%, 25% and 50%) of OSA were added to obtain high-polymerization debranched starch with different degrees of substitution. The reaction was carried out at 50°C for 6 hours. Finally, the pH was adjusted to 6.5 by 0.1M HCl to terminate the reaction. The obtained OSA debranched starch solution was washed with ethanol and centrifuged to obtain a precipitate, and then the precipitate was filtered and air-dried to remove water and ethanol, and finally freeze-dried to obtain the sample.

[0036] 3. Determination of the degree of substitution of OSA-modified debranched starch:

[0037] Accurately weigh 1g of OSA starch, place it in 15mL of HCl-isopropanol (2.5mol / L), stir at room temperature (20min), add 100mL of 90% isopropanol to the sample, stir (10min) and filter. Wash the residue with isopropanol (90%) until no AgCl precipitate can be detected with 0.1mol / L AgNO3. Redissolve the residue in 250mL of distilled water, heat in a boiling water bath and stir (20min), and immediately titrate with 0.05mol / L standard NaOH solution, using unmodified starch as a blank. The calculation formula (1) for the degree of substitution (DS) is as follows:

[0038]

[0039] Wherein: 162 refers to the molar mass of glucose residues, in g / mol; 210 refers to the molar mass of OSA, in g / mol; A refers to the amount of octenyl succinic anhydride ester group per gram of OSA-modified debranched starch; the A value can be calculated by the following formula (2):

[0040]

[0041] Wherein: V refers to the volume of NaOH consumed by the OSA starch sample, in mL; V0 refers to the volume of NaOH consumed by the native starch sample, in mL; M refers to the molar concentration of the NaOH solution, in mol / L; W refers to the dry weight of starch, in g.

[0042] 4. Preparation of OSA-modified debranched starch-reinforced gelatin gel:

[0043] Preparation of OSA-modified debranched starch solution: Different concentrations (0, 0.1, 0.2, 0.6 and 1.0 g) of OSA-modified debranched starch were dissolved in 10 mL of distilled water, and the suspension was treated with ultrasound for 1 min, heated at 120° C. for 2 min, and then cooled to 45° C.

[0044] Preparation of gelatin solution: Add 2 g of gelatin into 10 mL of distilled water and swell for 30 min at room temperature, then heat at 45°C for 30 min to dissolve the gelatin. The gelatin must be fully dissolved.

[0045] Preparation of OSA-modified debranched starch reinforced gelatin hydrogel: 10 mL of OSA-modified debranched starch solution of different concentrations at 45°C was added to the gelatin solution (mixed in equal volumes), stirred at 45°C for 10 min until completely mixed, and poured into the mold. After standing at 4°C for 12 h, a composite hydrogel of gelatin and debranched starch nanoparticles, i.e., OSA-modified debranched starch reinforced gelatin hydrogel, was formed.

[0046] 5. Determination of mechanical properties of gel:

[0047] (1) Rheological determination: A rheometer was used with a PP50 probe (50 mm in diameter) and a gap of 1 mm between the probe and the plate. To record G' and G", a frequency sweep was performed in the frequency range of 0.1-100 rad / s with a constant strain amplitude of 1%.

[0048] (2) Full texture test: TPA test is carried out using a physical property tester with a P 0.5 probe (selected according to the sample size). The test speed is 0.5 m / s, and each sample is set to be compressed twice continuously with a maximum strain of 75%. The recorded structural parameters are hardness (g), elasticity, cohesion, viscosity (g), chewiness (g) and recovery.

[0049] (3) Compression test: The strain rate was measured with a P36R probe at 1 mm / s, and the probe covered the entire surface of the gel sample. The stress and strain data were recorded during the experiment.

[0050] (4) Fourier infrared spectrometer: Weigh about 1 mg of sample, grind it into fine powder in an agate mortar, and then mix and grind it thoroughly with about 100 mg of dry KBr powder. Pour the powder into a die and press it into a thin sheet for measurement. Draw an infrared spectrum by infrared spectroscopy analysis.

[0051] 6. Data Analysis:

[0052] Data analysis was performed using variance analysis in SPSS 27.0 (SPSS, USA) software, with significant differences at the 95% (P﹤0.05) level, and origin mapping software was used to visualize the data.

[0053] Example 2 Results Analysis

[0054] 1. Degree of substitution:

[0055] Table 1 Degree of substitution of debranched starch polymer modified by octenyl succinic anhydride (OSA)

[0056]

[0057] Note: The values ​​are expressed as mean ± standard deviation (n = 3). Different letters such as a, b, and c indicate significant differences in the same column (P < 0.05).

[0058] OSA reacts with debranched starch under mild alkaline conditions (pH=about 8.5) to undergo an esterification reaction, replacing some of the hydroxyl groups in the starch. DS is defined as the average number of OSA groups substituted on each glucose unit, which can be determined by titration or nuclear magnetic resonance. The degree of substitution (DS) is used to describe the degree of modification of OSA starch. Therefore, the present invention prepared three kinds of OSA-modified debranched starches (0.026, 0.123, 0.192) with different degrees of substitution (as shown in Table 1) by controlling the ratio of OSA addition (3%, 25% and 50%) to debranched starch. As the amount of OSA added increases, the dehydroxylated ions of the hydroxyl groups on the starch molecules attack the carboxyl carbon on the OSA molecules, and the degree of starch substitution gradually increases, indicating that more hydroxyl groups in the starch molecules are replaced by OSA groups.

[0059] 2. Gelation:

[0060] Different concentrations of OSA-modified debranched starch (5%, 10%, 30%, 50%) solutions were added to the gelatin solution and mixed thoroughly, then poured into a square mold and left to stand at 4°C for 12 hours to form a gelatin composite hydrogel reinforced with OSA-modified debranched starch. In this gelation process, OSA-modified debranched starch regenerates in the gelatin matrix through self-assembly to form a nano-scale starch structure, and the hydroxyl groups on the molecules and the amino groups on the gelatin form hydrogen bonds to strengthen the gelatin-short linear hydrogel.

[0061] like Figure 1 As shown in the figure, all gelatin hydrogels are complete cubes with good gelling properties. The gelatin hydrogel without modified debranched starch is transparent. With the continuous increase in the amount of OSA-modified debranched starch added, the transparency of the composite hydrogel becomes lower and lower, gradually becoming milky white. The reason may be that OSA-modified debranched starch increases the content of hydrophobic groups, which increase the interaction between gelatin molecules, form more cross-linking points, and make the gelatin network structure denser, thereby affecting the optical path inside the gel and reducing the transparency of the gel.

[0062] 3. Compression performance:

[0063] Figure 2 The stress-strain curves of gelatin hydrogels reinforced with different degrees of substitution (3%, 25% and 50%) and different amounts of OSA-modified debranched starch (0, 5%, 10%, 30%, 50%) are shown in Figure 2. The highest point of the curve represents the maximum compressive strength of the material. The curve suddenly drops after reaching the highest point, indicating that the material has broken. Figure 2 It can be seen that when the strain reaches 50%-65%, the curve suddenly drops, that is, the gel structure breaks, representing its maximum compressive resistance. Under the compression mode, the compressive stress of pure gelatin hydrogel at a compressive strain of 65% is 567g. With the addition of OSA-modified debranched starch, the compressive stress of OSA-modified debranched starch / gelatin composite hydrogel increases significantly (883-2076g), and the maximum can be increased by nearly 4 times. These results show that OSA-modified debranched starch plays an important role in the mechanical hardness of nanocomposite hydrogels. The reason may be that OSA debranched starch self-assembles to form microstructures such as nanoparticles or micelles / vesicles, which are filled in the gelatin network structure, thereby effectively strengthening the gel network structure and showing better compression properties. In addition, OSA-modified starch may increase non-covalent interactions in the gel network, such as hydrophobic interactions and electrostatic repulsion, thereby enhancing the mechanical properties of the gel.

[0064] OSA modified debranched starch with different substitution degrees showed different trends with the increase of addition amount. For example, for OSA0.03 sample, with the increase of OSA modified debranched starch addition amount, the compressive stress of OSA modified debranched starch / gelatin composite hydrogel showed a downward trend; when the sample was OSA0.25, the compressive stress of the composite hydrogel showed a trend of first increasing and then decreasing with the increase of OSA modified debranched starch addition amount, among which when the addition amount was 10%, the compressive stress could reach 2665g; when the substitution degree was increased to 50%, when the sample was OSA0.50, the compressive stress of the composite hydrogel showed a trend of first stabilizing and then decreasing with the increase of OSA modified debranched starch addition amount. The reason for the above phenomenon may be that different OSA modified debranched starch / gelatin composite hydrogels have an optimal cross-linking point or cross-linking filling structure (starch nanoparticles, micelles, vesicles, etc.), and the gel reaches the highest mechanical strength, which will decrease when it is lower or higher.

[0065] 4.Texture characteristics:

[0066] Table 2 Texture properties of OSA-modified debranched starch-enhanced gelatin hydrogels

[0067]

[0068]

[0069] Note: 0 is unmodified gelatin hydrogel, OSA0.03, OSA0.25, OSA0.50 are different OSA mass fractions, 5%, 10%, 30% and 50% are different concentrations of OSA-modified debranched starch in reinforced gelatin hydrogel. These values ​​are expressed as mean ± standard deviation (n = 3). Different letters such as a, b, c, d, e indicate significant differences between the same columns (P < 0.05).

[0070] Table 2 shows the texture properties of OSA-modified debranched starch reinforced gelatin hydrogel: hardness, elasticity, cohesion, viscosity, chewiness and recovery. The sample was subjected to two compression tests by simulating the chewing movement of the oral cavity when a person eats through the texture analyzer probe, thereby obtaining a variety of texture characteristic parameters including hardness, cohesion, elasticity and viscosity. Hardness refers to the pressure required for the sample to achieve the set deformation during the first compression test; cohesion is the relative resistance of the sample to the second compression test after deformation after the first compression test, reflecting the difficulty of destroying the internal binding force of the system; elasticity is the degree to which the sample recovers to its original state after the first compression, which depends on the gel state of the sample; viscosity is a secondary indicator in the texture test, which is related to hardness and cohesion, and indicates the energy required to chew the semi-solid food into a swallowable state.

[0071] Compared with pure gelatin hydrogel, gelatin hydrogels reinforced with OSA-modified debranched starch of different mass fractions also showed significantly enhanced texture properties, indicating that OSA-modified debranched starch affects the structure and mechanical properties of gelatin hydrogel. OSA-modified starch self-assembles into nanostructures in situ and fills the gel network, and the hydrophobic groups can bind to the non-polar amino acid residues in gelatin through hydrophobic interactions, increasing the cross-linking density of the hydrogel network, thereby synergistically improving the hardness, adhesiveness and chewiness. The hydrogels composited with modified starches of OSA0.03 and OSA0.25 have higher hardness, adhesiveness and chewiness than the composite hydrogels of OSA0.50, indicating that modified starches with lower OSA mass fractions produce stronger gel networks. However, when the mass fraction is increased to OSA0.50, the hardness, adhesiveness and chewiness values ​​decrease, indicating that there is a critical content threshold. After exceeding this threshold, the addition of OSA modified groups no longer improves these properties, and may even make the gel network too tight due to excessive cross-linking, affecting water retention and distribution, thereby reducing the hardness, adhesiveness and chewiness of the gel. In short, the addition of modified starch with different OSA mass fractions and different concentrations of OSA modified starch has a significant strengthening effect on gelatin hydrogels. Practical applications can be changed accordingly according to the needs of different indicators, thereby expanding its practicality in food, medicine and other aspects.

[0072] 5. Dynamic rheological properties:

[0073] Figure 3 The dynamic rheological diagram of gelatin hydrogels strengthened with different degrees of substitution (3%, 25% and 50%) and different amounts of OSA-modified debranched starch (0, 5%, 10%, 30%, 50%). Storage modulus (G') and loss modulus (G"), where G' is used to characterize the storage energy of the gel, representing the gel behavior; G" is used to measure the energy dissipated in the form of heat, representing the sol behavior.

[0074] from Figure 3 It can be seen that at the same frequency, the storage modulus of all composite gels is higher than the loss modulus, indicating that the elasticity of the samples is higher than the viscosity, indicating that the composite gels are in a gel state. In addition, within the measured frequency range (0.1-100rad / s), there is no intersection between the two curves, indicating that the gelatin composite gel has a strong gel property. Figure 3It can be seen that the viscoelastic properties change from OSA0.03 to OSA0.25 and then to OSA0.50. At a fixed angular frequency, the more OSA-modified debranched starch is added, the larger the G' value is, indicating that the elasticity is stronger. The higher the concentration of OSA-modified starch in the gelatin hydrogel, the larger the G', indicating that the strength or elasticity of the gel is greater. With the increase of angular frequency, both G' and G" show an upward trend, indicating that gelatin is tightly combined with the OSA-modified starch matrix, which enhances the viscoelasticity of the hydrogel. In addition, the G' and G" of OSA0.25-50% are much higher than those of other mass fractions and other concentrations of reinforced gelatin. The results show that the mechanical properties and viscoelasticity of the hydrogel can be optimized by regulating the degree of substitution of debranched starch and the amount of OSA-modified starch added, thereby meeting the needs of different application fields, providing valuable guidance for its application in food processing and drug release, and also providing important theoretical support for its application development in the food and pharmaceutical industries.

[0075] Therefore, the present invention adopts the above-mentioned method for preparing OSA-modified debranched starch reinforced gelatin hydrogel, and the prepared hydrogel has excellent mechanical properties, thermal stability and elasticity, and has good anti-biodegradability, and can be widely used in food packaging, biomedicine and other fields.

[0076] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing OSA-modified debranched starch-reinforced gelatin hydrogel, characterized in that: The following steps are involved: S1. Preparation of debranched starch: using waxy corn starch as raw material, hydrolyzing the α-1,6 glycosidic bonds of amylopectin by pullulanase to produce debranched starch; S2. Preparation of debranched starch modified with octenyl succinate OSA: OSA reacts with debranched starch under mild alkaline conditions to replace part of the hydroxyl groups in the starch; S3. Preparation of debranched starch reinforced gelatin hydrogel modified with octenyl succinate OSA: adding the debranched starch solution modified with OSA into the gelatin solution to react and obtain the debranched starch reinforced gelatin hydrogel modified with OSA; The specific operations of step S2 are: 5% debranched starch was placed in an oil bath at 121°C for 30 minutes, then adjusted with 0.1M NaOH to maintain the solution pH at 8-9, and different mass fractions of OSA were added based on the mass of the debranched starch to react. After the reaction was completed, the precipitate was washed with ethanol and centrifuged to obtain a precipitate, and then the precipitate was filtered and air-dried to remove water and ethanol, and finally freeze-dried to obtain OSA-modified debranched starch with different degrees of substitution; the mass fraction of OSA was 3-50% based on the mass of the debranched starch; The specific operations of step S3 are: ① Preparation of OSA-modified debranched starch solution: dissolve OSA-modified debranched starch in distilled water, treat the suspension with ultrasonic wave for 1 min, then heat at 120° C. for 2 min, and then cool to 45° C. to obtain OSA-modified debranched starch solution; ② Preparation of gelatin solution: Add gelatin to distilled water, swell at room temperature for 30 minutes, and then heat at 45°C for 30 minutes to dissolve the gelatin to obtain a gelatin solution; ③ Preparation of OSA-modified debranched starch reinforced gelatin hydrogel: add OSA-modified debranched starch solution to gelatin solution, stir at 45°C for 10 min until completely mixed, pour into a mold, and let stand at 4°C for 12 h to form OSA-modified debranched starch reinforced gelatin hydrogel; In step ③, the volume ratio of the OSA modified debranched starch solution and the gelatin solution is 1:

1.

2. The preparation method according to claim 1, characterized in that: The specific operations of step S1 are: The waxy corn starch was dispersed in a phosphate buffer solution at pH 4.6, and then gelatinized for 40 minutes under continuous stirring in a boiling water bath. The fully gelatinized starch was cooled to 58°C, and pullulanase was added for enzymatic hydrolysis for 24 hours. The obtained hydrolyzate was first roughly centrifuged to obtain a supernatant solution, which was inactivated by boiling water bath for 15 minutes, and then centrifuged to remove the enzyme. Anhydrous ethanol was added to the obtained hydrolyzate, allowed to stand for 30 minutes, and then centrifuged and freeze-dried to obtain debranched starch.

3. The preparation method according to claim 1, characterized in that: In step S2, the reaction conditions of the debranched starch and OSA are 50° C. for 6 h, and then the pH is adjusted to 6.5 by HCl to terminate the reaction.

4. The OSA-modified debranched starch reinforced gelatin hydrogel prepared by the preparation method according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Controllable self-assembled starch nano-micelle as well as preparation method and application thereof

    CN115119948A

  • Preparation and application of OSA modified starch nanocrystal microcapsule

    CN115894977A